EVALUATING LANGUAGE FEATURES IN AN ENGLISH TEXTBOOKS FOR GRADE 11: A COMPREHENSIVE ANALYSIS BASED ON TEACHER AND EXPERT CRITERIA - Feby Rahmi; Muhammad Zaim (Indonesian EFL Journal, 2025)
This study is aimed to evaluate the English textbook, especially a textbook for grade 11 high school students. The source of data in this study is an English textbook that was used by Grade 11 high school students from the Ministry of Education and Culture of Indonesia. This study belongs to quantitative description approach to look at the phenomena to describe the existing condition in the field. The instrument of this research is an evaluation checklist. The evaluation checklist was filled out by two English teachers and the researcher itself. As a result of the study, textbook evaluation related to learning English is identified and classified based on the classification of language aspects which are evaluated based on developed criteria of textbook evaluation from some experts, like Celce-Murcia & Marianne (2001), Cunningsworth (1995), Littlejohn (2011), Mukundan (2011), Nation and Macalister (2010) and Ur (1996). Those results indicate that, the evaluation of an English textbook based on the language aspect for grade XI high school students. The quality of the English textbook based on the language aspect for grade XI high school students got an average score of 89,78%. It was classified as the category of Very Good. This demonstrates how well the textbook met the syllabus in terms of language quality, which can be seen from language appropriateness, where a match between language and student development, communicativeness, the coherence and unity of ideas, are integrated with four skills, and other language aspects, so the learning materials in this book are suitable with language aspect.